Electrodynamical Analyses of Dielectric and Metamaterial Hollow-core CylindricalWaveguides - Nickelson, L.; Gric, T.; Asmontas, S.; Martavicius, R. (Elektronika ir Elektrotechnika, 2008)
Development of computer algorithms for electrodynamical analyses of different waveguides is important nowadays due to the fact that these can be created from the newest materials with complicated dependences of the permittivity and the permeability on frequencies and waveguides can have nanometers sizes. We present the dispersion equation for analyzes of dielectric and metamaterial hollow-core cylindrical waveguides (HCWs). The main objective of our work is to analyze dispersion characteristics of the dielectric and metamaterial HCWs. We have analyzed dispersion characteristics of single−mode and many−mode dielectric and metamaterial HCWs. Dependencies of normalized propagation constant values on waveguide radiuses have been analyzed for dielectric and metamaterial HCWs. We have compared properties of the dielectric HCWs with metamaterial HCWs using obtained graphical results. Ill. 11, bibl. 10 (in English; summaries in English, Russian and Lithuanian).